BIM-based Competitive Advantages and Competitive Strategies for Construction Consultancy SMEs: A Case Study in Vietnam - Nguyen, The-Quan; Thieu-Thi, Thanh-Thuy; Vu, Nam-Ngoc (International Journal of Sustainable Construction Engineering and Technology, 2021)
Building Information Modelling (BIM) has been proven as an innovative approach to bring values to construction projects as well as stakeholders, including construction consultancy firms. BIM adoption could assist construction consultancy Small and Medium-sized Enterprise (SMEs) in enhancing their competitive capability. Using a case study with a pioneer BIM service providers which is an SME in Vietnam (the Consultant), the paper explores the core competences for delivering BIM services in relation with potential competitive advantages. Four typical BIM market segments have been discovered, which include: i) BIM strategic services, (ii) BIM services, (iii) BIM-enabled services, and (iv) BIM tools development. Exploring six BIM cases, the realized core competences of the Consultant which are reported in the paper include the BIM-related skillful human resources (both in-house and from external), BIM know-hows, reputation, and also the benefits from a BIM network that the Consultant established as an outcome of a granted BIM research project. Focusing on only the first three market segments, the Consultant has taken advantage of their core competences to deliver differentiation and focus strategies to compete and generate competitive advantages. Cost leadership strategies were not very successful in the case study due to that the economies of scale could not be met; however, they can be considered with the provision of BIM-enabled services, when BIM services are delivered together with other consultancy and/or construction services.